Recommendations on the use of magnetic resonance imaging in PSC‐A position statement from the International PSC Study Group. Issue 5 (29th September 2017) - Schramm, Christoph; Eaton, John; Ringe, Kristina I.; Venkatesh, Sudhakar; Yamamura, Jin; ,
Abstract : Primary sclerosing cholangitis (PSC) is a chronic cholestatic liver disorder characterized by inflammation and fibrosis of the intra‐ and/or extrahepatic bile ducts. Magnetic resonance imaging (MRI) is a noninvasive imaging modality that can be used to diagnose PSC and detect disease related complications. Quantitative MRI technologies also have the potential to provide valuable prognostic information. Despite the potential of this imaging technology, the clinical application of MRI in the care of PSC patients and imaging standards vary across institutions. Moreover, a unified position statement about the role of MRI in the care of PSC patients, quality imaging standards, and its potential as a research tool is lacking. Conclusion : Members of the International PSC Study Group and radiologists from North America and Europe have compiled the following position statement to provide guidance regarding the application of MRI in the care of PSC patients, minimum imaging standards, and future areas of research. (Hepatology 2017;66:1675–1688).